O! She doth teach the torches to burn bright: How JULIET can help authors and repository advocates. - Smith, Jane H (Association of Librarians and Information Professionals in the Social Sciences, 2007)
JULIET is a service provided by SHERPA. Its mission is to provide a brief summary of each funding agency’s policy on self-archiving of the published research they have funded. Each entry covers the requirements and details: -Whether archiving is mandatory or encouraged, -What should be deposited -Within what time frame this deposit should take place -Where articles should be deposited -Any conditions attached to this deposit.